Cost-effectiveness of a pediatric operating room installation in Sub-Saharan Africa. - Ava Yap; Salamatu I Halid; Nancy Ukwu; Ruth Laverde; Paul Park; Greg Klazura; Emma Bryce; Maija Cheung; Elliot Marseille; Doruk Ozgediz; Emmanuel A Ameh (Public Library of Science (PLoS), 2024)
The unmet need for pediatric surgery imposes enormous health and economic consequences globally, predominantly shouldered by Sub-Saharan Africa (SSA) where children comprise almost half of the population. Lack of knowledge about the economic impact of improving pediatric surgical infrastructure in SSA inhibits the informed allocation of limited resources towards the most cost-effective interventions to bolster global surgery for children. We assessed the cost-effectiveness of installing and running two dedicated pediatric operating rooms (ORs) in a hospital in Nigeria with a pre-existing pediatric surgical service by constructing a decision tree model of pediatric surgical delivery at this facility over a year, comparing scenarios before and after the installation of the ORs, which were funded philanthropically. Health outcomes measured in disability-adjusted life years (DALYs) averted were informed by the hospital's operative registry and prior literature. We adopted an all healthcare payor's perspective including costs incurred by the local healthcare system, the installation (funded by the charity), and patients' families. Costs were annualized and reported in 2021 United States dollars ($). The incremental cost-effectiveness ratios (ICERs) of the annualized OR installation and operation were presented. One-way and probabilistic sensitivity analyses were performed. We found that installing and operating two dedicated pediatric ORs averted 538 DALYs and cost $177,527 annually. The ICER of the ORs' installation and operation was $330 per DALY averted (95% uncertainty interval [UI] 315-336) from the all healthcare payor's perspective. This ICER was well under the cost-effectiveness threshold of the country's half-GDP per capita in 2020 ($1043) and remained cost-effective in one-way and probabilistic sensitivity analyses. Installation of additional dedicated pediatric operating rooms in Nigeria with pre-existing pediatric surgical capacity is therefore very cost-effective, supporting investment in children's global surgical infrastructure as an economically sound intervention.